2009
DOI: 10.1007/s00436-009-1622-7
|View full text |Cite
|
Sign up to set email alerts
|

Experimental model in rats for study on transmission dynamics and evaluation of Clonorchis sinensis infection immunologically, morphologically, and pathologically

Abstract: This study aims to gain a better insight into the transmission patterns and immunologic profile of Clonorchis sinensis infection and make a headway on the pathogenesis regarding cholangiocarcinoma and hepatic lesions. Experimental models orally infected by C . sinensis metacercariae were constructed in rats. Immunological assays were performed to measure serum level of IgA, IgE, IgG1, IgG2a, IFN-gamma, and IL-4. Infection parameters were assessed by worm recovery rate, eggs per gram faece and worm size. Pathol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 39 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Our results showed that Cs CB might be involved in the pathogenesis of C. sinensis -related hepatobiliary diseases as a component of ESP with antigenicity and immunogenicity. Indeed, C. sinensis adults dwell in the bile duct of host, persistently released ESP resulting in mechanical damage and chemical stimulus which must have brought on infiltration of inflammatory cells surrounding bile ducts and adenomatous hyperplasia of biliary epithelia [42-44]. However, there remains much to do to elucidate the mechanism of C. sinensis causing hepatobiliary diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that Cs CB might be involved in the pathogenesis of C. sinensis -related hepatobiliary diseases as a component of ESP with antigenicity and immunogenicity. Indeed, C. sinensis adults dwell in the bile duct of host, persistently released ESP resulting in mechanical damage and chemical stimulus which must have brought on infiltration of inflammatory cells surrounding bile ducts and adenomatous hyperplasia of biliary epithelia [42-44]. However, there remains much to do to elucidate the mechanism of C. sinensis causing hepatobiliary diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Two hundred and twenty-four C. sinensis -infected animals were collected in total (Table S1). Thirty-two metacercariae were isolated from fresh water fish in Guangdong and Guangxi provinces and were developed into adults in Sprague-Dawley rats using the standard method [15]. Genomic DNA from each adult worm was extracted using a commercial DNA extraction kit (Qiagen, Germany) according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…The previously described egg counting method [28] was employed to calculate eggs per gram feces (EPG) from weeks 4 post challenge infection. The experimental rats were sacrificed at week 6 post infection to recover adult worms from livers for worm burden evaluation.…”
Section: Methodsmentioning
confidence: 99%